PEMBELAJARAN MUFRODAT BAHASA ARAB DI TADIKA PASTI AS-SHARIFF KENINGAU MALAYSIA - Rina Dian Rahmawati; Devynta Aprilia; Anis Cahyati (Institut Pendidikan Tapanuli Selatan, 2023)
This study refers to three main problems, including the mufradat learning process in Pastika As-Shariff Keningau Malaysia, the problems that occur when the learning process is carried out and the efforts made to overcome the problems. The type of research that the author does is qualitative research. In this study, data collection was carried out by means of observation (observation), interviews / interviews, and documentation, the documentation in this study interviewed Arabic language teachers, vice principals, and students. The data analysis technique in this research is the data analysis method. Analysis of the data in this study, namely the qualitative analysis method was carried out before entering the field, during the field and after the field. The results of this study are: knowing the learning process carried out at Tadika Pasti Ashharif Keningau Malaysia, knowing the problems that occur when learning Arabic, and the efforts made by the teacher in solving these problems.